(untitled) (Global Journal of Science Frontier Research, 1969)
This work proposes the coefficients for Angstrom -Prescott type of model for the estimation of global solar radiation in Makurdi, Nigeria using relative sunshine duration alongside the measured global solar radiation data (2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010). The model constants a and b obtained in this investigation for Makurdi are .138 and 0.488 respectively. The correlation coefficient of 89% (P=0.00) between the clear sky index and relative sunshine duration, as well as the coefficient of determination, R2 of 79.5 obtained shows that this model fits the data very well. Hence, the very low mean standard error of 0.025 showed a good agreement between the measured and estimated global solar radiation. Consequently, the developed model in this work can be used with confidence for Makurdi, and other locations with similar climate conditions.